SF method for removing small skin melanocytic nevus - Zhang, Jianfei; Tan, Kaixi; Tang, Yujun; Xiao, Xia; Yang, Feng; Chen, Jie (Frontiers in Surgery, 2024)
The most prevalent benign skin tumor is a melanocytic nevus, which can potentially turn cancerous and frequently impair a patient's appearance.Objective To find a standardized surgical procedure for the removal of tiny skin pigmented nevis and to look into the effectiveness of the SF technique for doing so.Methods A retrospective study was conducted on 723 patients with small-sized pigmented nevi between June 2022 and June 2023. The nevi were removed using the SF method, and the patients' overall health and the duration of the procedure were recorded. Three months following the procedure, the patients completed a questionnaire to assess the effectiveness, recurrence, complications, and degree of satisfaction with the surgical outcome.Compared with the normal method, SF method had shorter operation time, higher effective rate, no recurrence and other postoperative complications after 6 months, less scar hyperplasia, and good evaluation satisfaction of all patients. No patient was rated as average or poor. No recurrence.The standardized surgical approaches for the small-size excision of melanocytic nevuses may be easily mastered by primary practitioners using the SF method, making it a valuable tool for practical use.